Diagnosing desmitis of the origin of the suspensory ligament. (2nd April 2015) - Meehan, L.; Labens, R.
Summary: Desmitis of the origin of the suspensory ligament is a common injury of sport horses; however, it remains a diagnostic challenge. The anatomy of the region can lead to difficulties localising the lameness. Diagnostic imaging may be complicated by overlying structures and the limitations of the imaging modalities readily available. A logical approach to clinical examination, diagnostic analgesia and multimodal imaging can help to overcome these difficulties.